A Rare Tumor in a Septuagenarian Female 16 Years After Radical Mastectomy for Breast Carcinoma - Mohammadhossein Rahimirad; Sara Daneshvar; Shaghayegh Rahimirad; Monireh Halimi; Akbar Sharifi (Clinical Case Reports)
ABSTRACT Pleuropulmonary spindle cell carcinoma (SpCC) is a very rare tumor that belongs to a subgroup of sarcomatoid carcinomas of non‐small cell carcinomas of the lung. Breast carcinoma is one of the most common malignancies associated with metachronous second primary cancers. To our knowledge, this is the first report of a rare case of multiple pleuropulmonary SpCC in a 70‐year‐old woman, 16 years after mastectomy and chemotherapy for breast carcinoma.